Desenvolvimento de código computacional para análise modal de treliças planas via método dos elementos finitos - Kobayashi, Felipe Camargo de Oliveira (2022)
This work aims to present a computational code capable of performing the modal analysis of plane trusses, providing the natural frequencies and vibration modes, which are essential elements in the Structural Dynamics field. Firstly, the equations required for the development of the computer program were presented. The introduced computer code is based on the Finite Element Method (FEM), and the MATLAB software was used for its design. Through the App Designer environment, an interface was developed to make it easier to insert all the data. To validate the results from the developed code, three very common plane trusses were chosen: Howe, Pratt and Warren. For comparison purposes, the Ansys Mechanical APDL 2022 R2 Academic Research was chosen, which is one of the most well-known Finite Elements Analysis software. From the results obtained by the developed computer program and Ansys Mechanical APDL, it can be state that all the results converge, proving the accuracy of the developed computer code.